Antidiabetes dari Fraksi Air Daun Karamunting (Rhodomyrtus tomentosa (Ait.) Hassk.) Terhadap Kadar Glukosa Darah Mencit Diabetes - Novia Sinata; Helmi Arifin (Fakultas Farmasi Universitas Andalas, 2016)
Karamunting is one of the plants used in traditional medicine of diabetes mellitus. The antidiabetic effect of aqueous fraction of Rhodomyrtus tomentosa (Ait.) Hassk leaves has been investigated on male white mice that were induced with alloxan dose 200 mg/kgBW intraperitoneally. The fraction was given orally at dose 10, 20, 40 mg/KgBW for 15 days. Parameters that were measured are decrease concentration of blood glucose, body weight, urin output and water intake. Result showed that the aqueous fraction of Rhodomyrtus tomentosa (Ait.) Hassk leaves at dose 10, 20, 40 mg/KgBW has effect on decreasing blood glucose level on diabetic mice induced alloxan (P<0.05). This fraction also improved body weight, urine output dan reduced water intake (P<0.05).